External Genitalia Myiasis in a 40-Year-Old Woman - Ghazal Mansouri; Leila Allahqoli; Hamid Salehiniya; Ibrahim Alkatout (Case Reports in Obstetrics and Gynecology)
Human myiasis is an infestation produced by fly larvae invading the tissues. We present a case of a 40-year-old virgin woman with vulvar myiasis. She reported at the gynecology clinic with a bloody discharge, severe pain, and swelling of the genital area for six days. Her menstrual history revealed the use of folded clothes. She had no specific gynecological disease. At the examination of the external genitalia, a tender mass measuring 6 cm×4 cm and an ulcer measuring 1 cm×1 cm on the surface of the labia majora were found. The patient was hospitalized. Serology, blood, and urine tests were requested; all laboratory tests were normal. The patient was transferred to the operating room (OR) with the diagnosis of necrotizing fasciitis. In the OR, we performed a longitudinal incision on the mass and removed nearly 30 visible maggots. After washing with normal saline, the patient was transferred to the ward without wound suturing. Debridement of the necrotic vulvar mass along with daily washing was performed for 7 days. The wound was sutured on the seventh day at the OR. Antibiotic therapy was continued for 4 days, and the patient was discharged with normal laboratory tests on the eleventh day after admission. We believe that poor sanitary hygiene was the cause of vulvar myiasis in our patient. We conclude that appropriate measures must be taken to reduce the risk of human myiasis, especially in tropical rural regions.